The youth dividend and agricultural revival in India - Narayanan, Sudha; Vijayabaskar, M.; Srinivasan, Sharada (Springer, 2023)
Fifty-four per cent of India’s population is under 25 years of age and, as per the 2011 Population Census, close to 34 per cent of India’s rural population belonged to the age group 15–34. While the presence of a sizeable young population is believed to offer a demographic dividend, policy efforts to realize the dividend have not met with success. Poor prospects for livelihoods within agriculture, its declining importance as a sector in the national economy, and aspirations of rural youth and their parents to find futures in nonfarm sectors suggest that, like elsewhere, agriculture today is an unlikely option for the young in India. The chapter brings the question of youth in agriculture into focus. Despite a large share of rural youth involved in farming, there is limited research or policy attention on the issues and challenges that they face around farming, non-farm opportunities, succession, and intergenerational transfer of resources and knowledge. It makes the case for improving the livelihood prospects within agriculture in a context of changing youth aspirations. We argue that a clearer understanding of the issues is essential to frame a nuanced approach to support the role of youth in agriculture and the role of agriculture in youth livelihood strategies.